An automated method for the microbiological assay of serum pyridoxal - Davis, R. E. (1973)
A fully automated method for the measurement of serum pyridoxal has been developed. Acid phosphatase was used for dephosphorylation and precipitation of the serum proteins was not required. A chloramphenicol-resistant strain of L. casei was used as the test organism and this removed the need for sterilization. The method gives highly reproducible results, and is suitable for population and institutional studies.